2015
DOI: 10.1186/s12910-015-0035-7
|View full text |Cite
|
Sign up to set email alerts
|

Understandings of genomic research in developing countries: a qualitative study of the views of MalariaGEN participants in Mali

Abstract: BackgroundObtaining informed consent for participation in genomic research in low-income settings presents specific ethical issues requiring attention. These include the challenges that arise when providing information about unfamiliar and technical research methods, the implications of complicated infrastructure and data sharing requirements, and the potential consequences of future research with samples and data. This study investigated researchers’ and participants’ parents’ experiences of a consent process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…Findings from this study point to the need to de-emphasise the role of experts (doctors and other health workers) and institutions (health facilities), and to instead principally engage community members and spaces as a means of obtaining adequately informed consent for research participation. Indeed, our findings suggest that, on reflection, our interviewees felt that they had consented to participate without adequate information about the study, which echoes findings from several previous studies (Robinson, Slashinski, Wang, Hilsenbeck, & McGuire, 2013;Traore et al, 2015).…”
Section: Discussionsupporting
confidence: 84%
“…Findings from this study point to the need to de-emphasise the role of experts (doctors and other health workers) and institutions (health facilities), and to instead principally engage community members and spaces as a means of obtaining adequately informed consent for research participation. Indeed, our findings suggest that, on reflection, our interviewees felt that they had consented to participate without adequate information about the study, which echoes findings from several previous studies (Robinson, Slashinski, Wang, Hilsenbeck, & McGuire, 2013;Traore et al, 2015).…”
Section: Discussionsupporting
confidence: 84%
“…Investigators examining consent to genomic research in African settings have identified a number of challenges in communicating study goals, methods and procedures. 12–14 40 This is compounded by difficulties in finding equivalent terminology to explain pertinent concepts in local languages. 12 In our examination of consent documents, we found that researchers sought to find layperson explanations of some of the difficult concepts in genomics.…”
Section: Discussionmentioning
confidence: 99%
“…This may be particularly challenging in rural populations, where greater efforts and more time are likely to be needed to effectively explain data sharing. In practice, research participants may not feel that information about data sharing is a priority to engage with and understand, in comparison with the information they receive about potential benefits, harms and burdens of the biomedical study from which data will be shared [ 42 , 43 ]. In such circumstances, concerns arise that too much information about data sharing may ‘crowd out’ information about the biomedical study from which data are to be shared, and adversely impact participants’ understandings of the study [ 26 ].…”
Section: Discussionmentioning
confidence: 99%